Robert Frager's Perception of Qalb with Sigmund Freud's Psychoanalytic Theory (Comparative Study) - Sari, Maemunah Indah; Marjani, Gustiana Isya; Ratnasari, Juni; Khairunnisa, Keisya Azizah (Jurnal Riset Agama, 2023)
The study has the background that between the human heart and the mind there must be synchronization in order for good behavior. The study was intended to identify Robert frager's view of qalb with the Sigmund Freud's theory of psychoanalysis and also to a ratio between qalb Robert Frager and psychoanalysis Sigmund Freud. The study is qualitative in style with the method of library research that uses comparative analysis to compare qalb's opinion with sigmund Freud's psychoanalysis. Qalb is a place where man attains his individuality to spiritual, spiritual knowledge, and human consciousness, and helps one to believe in something. Psychoanalysis is all human behavior based on unconsciousness. The study may conclude that qalb, with personalities, is indeed different. But in reality humans cannot rely on one aspect to do something good. Instinct is needed as an inducement for the personality to direct one's behavior, but man needs the heart as his guide.